Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kunjungan Antenatal Care Di BPM Sukianti Kec. Sinaboi Kab. Rokan Hilir Tahun 2023 - Amalia Fajrika; Khairunnisa Situmorang; Rosmani Sinaga; Anna Waris Nainggolan (STIKes Ibnu Sina Ajibarang, 2023)
The service provided to women during pregnancy is ANC services. The aim of this ANC examination is to reduce the number of deaths and morbidity rates in pregnant women. This study aims to determine the relationship between knowledge and attitudes of pregnant women with antenatal care visits at BPM Sukianti Kec. Sinaboi District. Rokan Hilir 2023. This type of research is an analytical survey with a cross-sectional research design. The population is a total sampling, namely all pregnant women in BPM Sukianti District. Sinaboi District. Rokan Hilir in 2023 as many as 30 people. The data analysis technique uses chi square. The results obtained in this study were mostly good knowledge with 18 people attending antenatal care visits (60%) and positive attitudes of pregnant women with 18 people completing antenatal care visits (60%). Based on the results of the chi square test, there is a relationship between pregnant women's knowledge and antenatal care visits with a P value = 0.002 < 0.05, there is a relationship between pregnant women's attitudes and antenatal care visits with a P value = 0.008 < 0.05. The conclusion is that there is a relationship between knowledge and attitudes of pregnant women and antenatal care visits. It is recommended that pregnant women provide antenatal care services according to standards and in a complete manner so that they can reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia.